The Phenomenon “Time” and its Parameters (Attempt for a Psychological Analysis) - Milkov, Luchiyan (Research Papers, 2011)
A philosophical understanding of time models is characterized by a long and a complex way of interpretation of the personality’s knowledge activity. It is also characterized by the formation of temporal picture of the world and the person’s orientation in time.Time’s main models are explored: first one known in the phylogenesis –mythological. Then we move to other models such as cyclic, linear, axis, existence time. The phenomenon of ‘mixing times ‘ or ‘time existence’ is a result of another spatial model – not linear or branched time. The creation of social time is examined as part of the anthropocentric time.In the personality’s mentality psychological time reflects on the time relations of its life events. The human being and its life along with events occurring throughout that life build up living time. That is recognized as a simultaneousness, succession and duration of the events and the processes as well as speed and belonging to the present, past and the future. Towards these time features the following can be added – the experiences of compression, interruption and none- interruption, restriction and none restriction, acknowledgment of age, perception of life and death, perception of the probable life expectancy and the connection between one’s own life and the life of past and future generations as well as the whole mankind.